2021
DOI: 10.7554/elife.64557
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 regulates the threshold of B cell activation and autoimmunity

Abstract: Despite the mechanisms of central and peripheral tolerance, the mature B cell compartment contains cells reactive for self-antigen. How these cells are poised not to respond and the mechanisms that restrain B cell responses to low-affinity endogenous antigens are not fully understood. Here, we demonstrate a critical role for the glycan-binding protein galectin-9 in setting the threshold of B cell activation and that loss of this regulatory network is sufficient to drive spontaneous autoimmunity. We further dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our previous works demonstrated that CB-SCs displayed PD-L1 (CD274) [32] and herpesvirus entry mediator (HVEM, CD270) [5], which contributed to the immune modulations of CB-SCs on T cells. To reveal the molecular mechanisms underlying the immune modulation of CB-SCs on B cells, we further explored other potential surface molecules such as galectins [28,33], which are involved in the immune suppression of human mesenchymal stem cells (MSC) on both T and B cells [26,34]. Galectins have been recognized as essential regulators contributing to the induction of an immune tolerance and homeostasis, therefore functioning as attractive therapeutic targets for attenuating autoimmune and inflammation disorders [23,35].…”
Section: The Expression Of Gal-9 On Cb-scs Acts As a Key Molecule Con...mentioning
confidence: 99%
“…Our previous works demonstrated that CB-SCs displayed PD-L1 (CD274) [32] and herpesvirus entry mediator (HVEM, CD270) [5], which contributed to the immune modulations of CB-SCs on T cells. To reveal the molecular mechanisms underlying the immune modulation of CB-SCs on B cells, we further explored other potential surface molecules such as galectins [28,33], which are involved in the immune suppression of human mesenchymal stem cells (MSC) on both T and B cells [26,34]. Galectins have been recognized as essential regulators contributing to the induction of an immune tolerance and homeostasis, therefore functioning as attractive therapeutic targets for attenuating autoimmune and inflammation disorders [23,35].…”
Section: The Expression Of Gal-9 On Cb-scs Acts As a Key Molecule Con...mentioning
confidence: 99%
“…This can suppress B cell receptor (BCR) signalling through CD45-mediated recruitment of SHP1 (refs. 55 , 56 ), resulting in an inhibition of B cell activation and their subsequent differentiation into plasma cells 57 . Likewise, changes in the glycosylation of surface proteins of B cells can impact the binding of extracellular galectin-1 and galectin-8 and affect B cell differentiation.…”
Section: Regulation Of Adaptive Immunitymentioning
confidence: 99%
“…The regulatory power of GBPs is not limited to T cells, having also a key role in B-cell development and maturation in which stromal cell derived-galectin-1 may serve as a ligand for pre-BCR signaling [ 46 ]. In this regard, recent evidence highlights the critical role of galectin-9 in setting the threshold of B-cell activation, by regulating the interactions between the BCR and Toll-like receptors (TLRs); loss of this regulatory network was associated with development of autoimmunity [ 47 ]. Similar to T cells, GnT-V-mediated N -glycan branching has also been shown to promote positive selection of B cells by increasing pre-BCR/BCR signaling via CD19 surface retention.…”
Section: Introductionmentioning
confidence: 99%